An exerciSe program to improve depression And sleep Disorders in oncology patients: The SAD study. (December 2018) - Kozik, Teri M.; Hickman, Mary C.; Schmidt, Sherri; Connolly, Therese F.; Paustenbach, Kim; Vosti, Paul; Bhattacharyya, Mouchumi
Abstract: Purpose: The purpose of this study was to determine if a structured supervised outpatient exercise program specifically for cancer patients would be associated with improvements in insomnia and depression after attending for 10-weeks. Design: Descriptive observational study. Sample and setting: 75 adult subjects attended an outpatient hospital based exercise program specifically for cancer patients and coordinated by an exercise physiologist and a physical therapist. Method: Two validated instruments were administered to measure insomnia (Athens Insomnia Instrument) and depression (Zung Self-Rating Depression Scale) at baseline (prior to the start of the program) and repeated after 10-weeks of exercise. Results: Forty (53.3%) completed the full 10 week program. Of the 40 that completed the program, an improvement in insomnia scores was seen (p-value<0.01) as well as depression scores (p-value = 0.01). Baseline insomnia scores were not different between subjects that did not complete the program compared to those who did (p-value = 0.4401). However, baseline depression scores were higher in subjects who did not complete the program compared to subjects who did (p-value = 0.0462). Conclusions: Exercise improved depression and insomnia in cancer patients. By improving these symptoms, mortality, morbidity, and costs may be improved in the oncology population. Exercise programs can provide not only the health benefits of exercise, but also give cancer populations support from their peers which may improve their overall quality of life. Highlights: A structured exercise program is associated with improved insomnia scores in oncology patients. A structured exercise program is associated with improved depression scores in oncology patients. Baseline depression scores can affect attrition rates in oncology patients who start a structured exercise program.